1995
DOI: 10.1037/0021-843x.104.1.205
|View full text |Cite
|
Sign up to set email alerts
|

A priming methodology for studying self-representation in major depressive disorder.

Abstract: The authors investigated processing of self-descriptive emotional information in depression using a modified Stroop color-naming task. Depressed (n = 58) and nondepressed control (n = 44) participants were required to name the color in which positive and negative adjectives, differing in the degree to which they described the person, were presented. These target adjectives were primed by emotional phrases that also varied according to degree of self-reference. Analyses indicated that depressed participants sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
100
1
7

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(119 citation statements)
references
References 41 publications
11
100
1
7
Order By: Relevance
“…This finding is inconsistent with previous studies that have utilised emotional versions of the Stroop colour-naming task to investigate attentional processing of emotional stimuli in patients with MD (e.g. Gotlib & Cane, 1987;Nunn, Mathews & Trower, 1997;Segal et al, 1995), as they reported interference from negative as opposed to positive stimuli. However, it should be noted that the observed difference in the present study failed to reach conventional significance and thus would require replication with a larger sample before any implications could be considered.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…This finding is inconsistent with previous studies that have utilised emotional versions of the Stroop colour-naming task to investigate attentional processing of emotional stimuli in patients with MD (e.g. Gotlib & Cane, 1987;Nunn, Mathews & Trower, 1997;Segal et al, 1995), as they reported interference from negative as opposed to positive stimuli. However, it should be noted that the observed difference in the present study failed to reach conventional significance and thus would require replication with a larger sample before any implications could be considered.…”
Section: Discussioncontrasting
confidence: 56%
“…For example, studies that have utilised emotional variants of the Stroop colour-naming task (e.g. Gotlib & Cane, 1987;Nunn, Mathews & Trower, 1997;Segal et al, 1995) have tended to demonstrate that depressed individuals are slower to colour-name depression-relevant words than positive or neutral words (usually interpreted as evidence of attention capture by the negative material). It has also been reported that patients with depression exhibit biased attentional processing of emotional faces (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It has been viewed as the cognitive aspect of self-concept (e.g., Higgins, Van, & Dorfman, 1988;Posner & Warren, 1972). In studies of self-representation, the modified Stroop (1935) color naming task has often been used to explore the cognitive characteristics of self-concept in different situations (e.g., Mikulincer, Dolev, & Shaver, 2004;Segal, Gemar, Truchon, Guirguis, & Horowitz, 1995). In the present study, we also used a modified Stroop color naming task to examine the change of self-representation under different experimental conditions.…”
Section: Self-esteem and Self-representationmentioning
confidence: 99%
“…Mismatch between the color and content of the word (e.g., the word "green" printed in red) typically results in a longer response latency, which has been typically regarded as evidence of cognitive interference. Modified versions of Stroop tests presenting emotional threat words have been used to examine attentional biases in numerous conditions, including depression (Klieger & Cordner, 1990;Segal, Truchon, Gemar, & Guirguis, 1995;Segal & Vella, 1990), panic disorder (McNally et al, 1994;McNally, Riemann, & Kim, 1990;McNally, Riemann, Louro, Lukach, & Kim, 1992), obsessive-compulsive disorder (Foa, Ilai, McCarthy, Shoyer, & Murdock, 1993;Lavy, Vanoppen, & Vandenhout, 1994), posttraumatic stress disorder (Foa, Feske, Murdock, Kozak, & Mccarthy, 1991;Kaspi, McNally, & Amir, 1995;McNally, English, & Lipke, 1993), specific phobia (Lavy, Vandenhout, & Arntz, 1993;Mathews & Sebastian, 1993), and SAD (Becker, Rinck, Margraf, & Roth, 2001;Hope, Rapee, Heimberg, & Dombeck, 1990;Lundh & Ost, 1996;Maidenberg, Chen, Craske, Bohn, & Bystritsky, 1996;Mattia, Heimberg, & Hope, 1993;McNeil et al, 1995;Spector, response latencies to threat words in contrast with non-threat words have been deemed to indicate selective attention towards the threat.…”
Section: Emotional Stroop Testmentioning
confidence: 99%